OPTIONS FOR TESTING KINEMATIC GPS MEASUREMENTS IN TERMS OF ACCURACY - Sedlak, Vladimir (European Scientific Journal, ESJ, 2014)
Accuracy of GPS kinematic measurements is analysed. Several GPS apparatus were tested in the geodetic network stabilized in the Central Slovak Region. GPS measurements were complemented by 2D terrestrial measurements using total stations. Possibilities of using the tested GPS apparatus and selected kinematic GPS methods were considered for their application for a purpose of real estate register, geological survey and GIS applications.